Remarks at the National Press Club Headliners Luncheon - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, discussed building new foundations of human solidarity, at a time when those foundations are questioned and even under attack. Peace and stability are critical to our efforts to grow economies and help people lift themselves out of poverty. He reviewed the work of the World Bank Group, especially over the past three decades, and outlined the pillars of the current strategy: accelerating inclusive, sustainable economic growth, building resilience to overlapping shocks and crises, and investing more and more effectively in people.